Detailed design of the large-bore 8 T superconducting magnet for the NAFASSY test facility. (5th February 2015) - Corato, V; Affinito, L; Anemona, A; Vetrella, U Besi; Zenobio, A Di; Zignani, C Fiamozzi; Freda, R; Messina, G; Muzzi, L; Perrella, M; Reccia, L; Tomassetti, G; et al.
Abstract: The 'NAFASSY' (NAtional FAcility for Superconducting SYstems) facility is designed to test wound conductor samples under high-field conditions at variable temperatures. Due to its unique features, it is reasonable to assume that in the near future NAFASSY will have a preeminent role at the international level in the qualification of long coiled cables in operative conditions. The magnetic system consists of a large warm bore background solenoid, made up of three series-connected grading sections obtained by winding three different Nb3 Sn Cable-in-Conduit Conductors. Thanks to the financial support of the Italian Ministry for University and Research the low-field coil is currently under production. The design has been properly modified to allow the system to operate also as a stand-alone facility, with an inner bore diameter of 1144 mm. This magnet is able to provide about 7 T on its axis and about 8 T close to the insert inner radius, giving the possibility of performing a test relevant for large-sized NbTi or medium-field Nb3 Sn conductors. The detailed design of the 8 T magnet, including the electro-magnetic, structural and thermo-hydraulic analysis, is here reported, as well as the production status.